Creative versus repetitive dance therapies to reduce the impact of fibromyalgia and pain: A systematic review and meta-analysis. (May 2022) - Murillo-Garcia, Alvaro; Adsuar, Jose C.; Villafaina, Santos; Collado-Mateo, Daniel; Gusi, Narcis
Abstract: Background and purpose: Physical exercise is one of the most effective interventions to reduce fibromyalgia symptoms. Previous studies have reported benefits of dance-based intervention on the fibromyalgia impact, health-related quality of life and pain, regardless the interventions were based on creative- or repetitive dance. This study aimed to compare the effectiveness of creative and repetitive dance interventions. Methods: PRISMA guidelines were followed in this systematic review. The Cochrane Library, PubMed, Trip, Google Scholar, Web of Science (WOS), Embase and Scopus databases were selected to identify potential articles. Studies were included if they met the following inclusion criteria: to be a clinical trial or a randomized controlled trial, include people with fibromyalgia, have a comparison group and evaluate the impact of the disease, pain or quality of life. Fifteen articles fulfilled the inclusion criteria. The methodological quality of the studies was assessed using the Cochrane Collaboration's tool. Results: Dance-based interventions significantly reduced fibromyalgia impact (standardized mean difference = −0.69), pain (standardized mean difference = −0.70 and increased quality of life (standardized mean difference = 0.43) of people with fibromyalgia. The effectiveness of dance interventions is increased when a creative component is added, since it can lead to higher improvements in pain, impact of the disease and improving quality of life. Conclusion: Dance-based interventions are significantly effective in reducing the impact of fibromyalgia, pain as well as increasing health-related quality of life. Subgroup analyses suggest that creative dance-based interventions could be more effective than repetitive dance-based interventions to reduce pain and fibromyalgia impact. However, results must be taken with caution due to the large heterogeneity and the small number of articles. Highlights: Dance-based interventions may be effective at reducing the impact of the fibromyalgia and pain and increasing health-related quality of life. Creative dance interventions may be more effective than repetitive dance intervention to reduce the impact of the fibromyalgia and pain. Dance interventions may also improve quality of life for fibromyalgia women.